Local Leadership and the Affordable Care Act - Williams, Stephen L. (J Public Health Manag Pract, 2015)
Local health departments are in key positions to lead in the education and implementation efforts to advance the Patient Protection and Affordable Care Act. The first enrollment period is over, but the efforts to enroll the uninsured and advocate for expansion of Medicaid in the states that have not yet taken on this expansion will continue for years to come. Political climates may be unsupportive, but some actions may still be possible.